Biennial culture or grassroots globalisation?: the challenge of the Picha art centre, as a tool for building local relevance for the Rencontres Picha, Biennale de Lubumbashi. - Mudekereza, Patrick Bulonza (My University, 2017)
This research aims to examine how the organisation of a biennial and its content could influence the modelling of an independent art centre. Using the concept coined by Arjun Appadurai, ‘grassroots globalisation’, this research unpacks the establishment of Picha art centre through its project Rencontres Picha, Biennale de Lubumbashi (2010-2013), a case study, in examining how specificities of the global south geopolitics may encourage alternative art institutions to emerge. By studying the first three years of Picha through the project Rencontres Picha, Biennale de Lubumbashi (2010-2013), this research investigates how the art centre was created as a tool to position the organisation within the global art discourse whilst maintaining its local relevance in Lubumbashi. It is located at the intersection of three areas of study: Biennial culture, alternative institution models, and global South strategies and politics.
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Arts in (History of Art), 2017
Keywords: Art, Modern--Exhibitions